(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
This study examined the impact of forest loss by fragmentation along four communities that taboo the species of primates and reptiles. Data by survey at three sighting regimes in a3×2×5 factorial experiments were square root-transformed before the analysis of variance and significant means separated at 5% level of probability with the Duncan multiple range tests. The fineness/coarseness of forest corridors and edges, availability of propagules and a-subjective habitat-matrix score for 7 key attributes of forest fragmentation along with soil samples analyzed for CEC, exchangeable cations and Ca-Mg ratio. Results showed higher mean population sighted in corridors than that of the edges. Propagule availability was Ugili Amai-Olloh Ossisa (18.5 kg/ha) >Ugono-Orogun (16.8 kg/ha)>Umute-Nsukwa (15.2 kg/ha)>Emu Uno (10.8 kg/ha) and underpinned intact fragment as Umute-Nsukwa>Ugili-Ossisa>Ugono-Orogu> Emu-Uno for the protection of IUCN Red List vulnerable white-throated guenon (Cercopithecus erythrogaster) and threatened West African dwarf crocodile (Osteollaemus tetraspis). Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 29-38